Advancing Customary Village Development in Bali Through Community Participation: Do Village Government Roles Matters? - Heryanda, Komang Krisna; Dharmayasa, I Putu Arya; Suwena, Kadek Rai; Irwansyah, M. Rudi (Journal of Accounting Research, Organization and Economics, 2023)
Objective The provision of customary village funds in Bali can be viewed as a governmental initiative aimed at the preservation of cultural heritage. For the effective implementation of customary village development, it is imperative to involve the community directly and also acknowledge the role of the government.Methodology The research was conducted in the Province of Bali with 94 customary villages as research objects. The methodology employed for data collection involved the distribution of questionnaires to the leaders of customary villages. The data was subsequently processed using moderation regression analysis, supplemented by interviews to augment the information provided by the respondents.Results The study's findings indicate that the involvement of the community had a significant impact on the growth of conventional villages in Bali. The mobilisation of resources by the village government can potentially enhance the impact of community participation on the development of customary villages in Bali.Research limitations/implications This research only reveals the success of customary village development in terms of community and government participation. This research has the impact that it is necessary to pay attention to the development of traditional villages to maintain local wisdom so that harmonization in society can be realized.Novelty/Originality The originality of this research found that even though there is a separation of authority between the village government and customary village, the village government is still allowed to mobilize the community to be involved in the development of customary village so that environmental and cultural preservation can be achieved.